Meningkatkan Mutu Beton dengan Penggunaan Fly Ash serta Variasi Merk Semen - Fahrul Adi Pangestu; Rio Rahma Dhana (Faculty of Engineering, Kadiri University, 2021)
The continuous use of Cement on concrete will adversely affect environmental conditions. In addition, the cost of Cement that is not cheap makes concrete production less efficient. The use of alternative materials should be considered to get good quality concrete as efficiently as possible. This study aims to compare concrete quality with different variations of cement trademarks using fly ash added material. The method used is an experimental method with the manufacture of samples in the laboratory. Added fly ash variations of 0%, 5%, 7%, 9% of cement weight. The samples used are cylindrical. With the number of samples on every variation as much as two samples. They were compressive strength conducted at the age of concrete 7 and 28 days. The study results obtained the highest compressive strength at the age of concrete 7 days obtained in concrete samples with the use of Gresik cement substituted fly ash as much as 5%, which amounted to 16.14 Mpa. While the highest compressive force at the age of concrete 28 days obtained in concrete samples with the use of milk substituted fly ash as much as 5%, namely 22.65 Mpa.